Advances and Challenges in Remote Sensing Technology for Hydrologic Environment Monitoring - Ran, Qirui (Transactions on Environment, Energy and Earth Sciences, 2024)
Water is essential for human life and aquatic organisms. However, with industrial development spreading across the world, the hydrologic environment is not as stable as before due to various types of pollution. Monitoring the hydrologic environment and detecting potential threats are necessary processes. Remote sensing technology plays a key role in many monitoring processes. Since its discovery and extensive use, remote sensing technology has provided people with various types of Earth data. It is also a suitable solution for monitoring and detecting the hydrologic environment. By providing detailed data of aquatic areas, remote sensing technology can predict different situations, allowing corresponding responses to protect the environment. Recently, several studies on remote sensing technology have made significant progress; however, new challenges stand in the way of future studies on the topic. This paper gives an overview of recent studies on remote sensing technology as well as hydrologic signatures. It also discusses challenges in the field and offers suggestions for future research.